Geneologi Hermeneutika Hukum Islam (Fikih Kontekstual ‘Umar Bin Al-Khaṭṭāb) - Anshori, Muhammad (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
This paper analyzes the thought or contextual interpretation of ‘Umar Ibn al-Khaṭṭāb which is closely related to hermeneutics. In the Islamic thought tradition, hermeneutics as a method of interpreting the holy book has been done in the early Islamic era. If we look at back ward, the Prophet Muhammad himself had done it. However, because the term hermeneutics that has developed in the Western world, so it feel foreign to the Islamic world. One of the classical Islamic thinkers who wasprogressive thoughts and transcend his time in undesrtanding or interpreting the Qur’an was ‘Umar. This is the geneology of contextual interpretation developed by modern-cotemporary thinkers. In the periodezation of Islamic history, the thoght of ‘Umar can be categorized as classical hermeneutic, because it happened in the early of Islamic period. The thought of ‘Umar was very contextual and progressive. Therefore, it is not suprising to say that he was one of the early hermeneut of The Muslim.